KURIKULUM PENDIDIKAN ISLAM: HAKIKAT DAN KOMPONEN PENGEMBANGANNYA - Futihatul Janah; Fuad Mafatichul Asror; Eko Purnomo (Universitas Islam Lamongan, 2022)
The curriculum is structured in such a way as to facilitate the delivery of material to students. The Islamic education curriculum is closely related to Islam's goals, namely forming a complete person and total servitude to God. Meanwhile, curriculum development occurs in line with the pace of development and the challenges of the times, as well as policies issued by the government. This study aims to unravel the nature of the development of the Islamic learning curriculum, which is formulated from various components that make up the curriculum. The study found that curriculum development needs to pay attention to aspects of objectives, materials, methods, and evaluation of learning. This research with the genre of library research also argues that the development of an Islamic curriculum must be based on the principles of monotheism, relevance, and contextuality.